2010
DOI: 10.4319/lo.2010.55.6.2317
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the optical properties of a particle suspension associated with viral infection of marine bacteria

Abstract: A laboratory experiment was conducted to examine the temporal dynamics of the particle size distribution (PSD) and associated optical variability caused by viral infection of marine heterotrophic bacteria. The PSD covering a broad range of particle size from < 50 nm to 200 mm was measured in parallel with the spectral particulate absorption and beam attenuation coefficients, from which the particulate scattering coefficient, b p (l), was determined. Within 12 h following infection, the host bacterial populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…It seems even more counter‐intuitive, therefore, that during our deployments the LISST‐100X reported a consistent fine tail, especially given the dynamism of in‐situ size distributions. Given the discrepancy between in‐situ imaging and LISST‐100X size distributions, and the similarity between LISST‐100X and distributions derived in the laboratory [e.g., Reynolds et al , 2010; Uitz et al , 2010], it seems that sample handling, preparation and the choice of analysis method itself (e.g., flow cytometery, optical microscope) cause significant discrepancies between instrumentation in most inter‐comparisons [see, e.g., Serra et al , 2001]. Caution against over‐interpretation of laboratory‐derived size distributions ought to be exercised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems even more counter‐intuitive, therefore, that during our deployments the LISST‐100X reported a consistent fine tail, especially given the dynamism of in‐situ size distributions. Given the discrepancy between in‐situ imaging and LISST‐100X size distributions, and the similarity between LISST‐100X and distributions derived in the laboratory [e.g., Reynolds et al , 2010; Uitz et al , 2010], it seems that sample handling, preparation and the choice of analysis method itself (e.g., flow cytometery, optical microscope) cause significant discrepancies between instrumentation in most inter‐comparisons [see, e.g., Serra et al , 2001]. Caution against over‐interpretation of laboratory‐derived size distributions ought to be exercised.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing error in laser diffraction measurements has also been noted by Reynolds et al [2010] for particle populations with poor sorting. Interestingly, Ahn and Grant [2007] observed that chemical and mechanical disaggregation of samples prior to analysis improved the agreement between LISST and optical microscopy and both Reynolds et al [2010] and Uitz et al [2010] have show almost 1:1 agreement in particle concentration and size between LISST and Coulter counter measurements for fine particles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the scattering and backscattering coefficients of suspended particles have been shown to provide useful proxies of mass concentration of total suspended particulate matter (SPM), particulate inorganic carbon (PIC), and particulate organic carbon (POC) in the ocean [5][6][7]. Multi-angle light scattering measurements provide a means to estimate the particle size distribution [8][9][10][11], including the submicrometer size range [12][13][14]. The angular pattern of light scattering can also contain useful information about the composition of particulate assemblages, including the bulk refractive index of particles [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying the temporal dynamics of phage impact and untangling the underlying ecological and evolutionary causal mechanisms could yield interesting insights but is beyond the scope of the present study. The resolution of our OD measures (Uitz et al 2010;Zwietering et al 1990) permits the detection of weak links, which is not always possible in other types of association, namely those that depend upon field sampling or the direct observation of rare interactions (Goldwasser and Roughgarden 1997;Olesen and Jordano 2002). Our bacteria-phage networks can be accessed online (http://dx.doi.org/10.6084/m9.…”
Section: Isolation Of Bacteria and Phagesmentioning
confidence: 99%